2016
DOI: 10.1002/cjoc.201500748
|View full text |Cite
|
Sign up to set email alerts
|

Cytidine Mediated AuAg Nanoclusters as Bright Fluorescent Probe for Tumor Imaging in vivo

Abstract: Noble metal clusters is an emerging class of fluorescent probes, avoiding most of the drawbacks of common fluorescent compounds, and they are simple to prepare and have good water solubility, good biocompatibility and excellent fluorescence properties. In this study, we have explored the synthesis of the cytidine mediated gold-silver nanoclusters (AuAg NCs) and applied it for both in vitro cellular imaging and tumor in vivo detection. Experimental results show that the as-prepared AuAg NCs can be used as a sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Although there are many interesting reports about the application of gold nanoclusters as fluorescent probes in vitro and in vivo , most of them concern mainly one-photon excitation properties of nanoclusters. On the other hand, two-photon luminescence microscopy (2PLM) has many advantages over traditional one-photon optical microscopy techniques such as possibility of high-resolution deep imaging even in highly scattering environments like living tissues, localized red or infrared excitation in small focal volume, and reduced phototoxicity and photobleaching.…”
mentioning
confidence: 99%
“…Although there are many interesting reports about the application of gold nanoclusters as fluorescent probes in vitro and in vivo , most of them concern mainly one-photon excitation properties of nanoclusters. On the other hand, two-photon luminescence microscopy (2PLM) has many advantages over traditional one-photon optical microscopy techniques such as possibility of high-resolution deep imaging even in highly scattering environments like living tissues, localized red or infrared excitation in small focal volume, and reduced phototoxicity and photobleaching.…”
mentioning
confidence: 99%
“…Interestingly, when the auranofin was used to treat arthritis, fluorescent nanoclusters were found in skin cells. Our group began to study the generation of fluorescent nanoclusters in mammalian cells for pathological biomedical imaging in situ. , Gold nanoclusters are formed in the cytoplasm of tumor cells, which will not happen in noncancer cells . Subcutaneous injection of chloroauric acid solution into the vicinity of xenograft tumor in nude mice with hepatocellular carcinoma or chronic myeloid leukemia can effectively synthesize fluorescent gold nanoclusters without significantly diffusing to surrounding normal tissues, and then perform fluorescence imaging of tumor in situ . Alzheimer’s disease may be caused by the accumulation of amyloid protein, which may be the key protein for the synthesis of nanoclusters. , Taking pathological mice as the experimental model, it was found that zinc gluconate could pass through the blood–brain barrier and generate specific fluorescent zinc nanoclusters in the hippocampus .…”
Section: Chemical Biomedical Imagingmentioning
confidence: 99%
“…The above study described the mechanism of uptake and manner of cell death and revealed its future applicability. In this trend, bright fluorescent cytidine-mediated Au-Ag NCs were developed by Chen et al and utilized for both in vitro cellular imaging and tumor in vivo detection [193]. The synthesis and tumor detective application of the above-acknowledged probe is shown in Figure 18.…”
Section: Bi-metallic Nanoclusters In Sensors and Bio-imagingmentioning
confidence: 99%
“…Figure 18. Scheme illustration of the process for cytidine mediated gold-silver nanoclusters (AuAg NCs) (Copyright Ref [193], WILEY publications).…”
Section: Bi-metallic Nanoclusters In Sensors and Bio-imagingmentioning
confidence: 99%